2019
DOI: 10.1021/acssuschemeng.9b05298
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed Single-Phase Ni2P Nanoparticles on N,P-Codoped Porous Carbon for Efficient Synthesis of N-Heterocycles

Abstract: Aerobic oxidative cross-dehydrogenative coupling represents one of the most straightforward and atom-economic methods for construction of C–C and C–X (X = N, O, S, or P) bonds, especially when environmentally friendly air is used as the oxidant. Herein, we report the development of an inexpensive, stable, and highly dispersed ultrafine Ni2P nanoparticles with narrow size distribution supported on N,P-codoped biomass-derived porous carbon. The as-prepared catalyst is highly active and stable for the synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 122 publications
0
41
0
Order By: Relevance
“…In literature, the synthesis of 2-substituted quinazolines is reported using the metal complexes and under "metal-free" conditions. [41][42][43][44] Although these reported methodologies are efficient but several shortcomings like use of organic solvents (dioxane, toluene, THF and ethyl acetate) as reaction media, strong oxidants, 'pure' oxygen environment, prolonged heating condition, green LED as irradiation source etc. are yet to Scheme 6.…”
Section: Visible Light Induced Photocatalytic Synthesis Of 2-quinazolinesmentioning
confidence: 99%
“…In literature, the synthesis of 2-substituted quinazolines is reported using the metal complexes and under "metal-free" conditions. [41][42][43][44] Although these reported methodologies are efficient but several shortcomings like use of organic solvents (dioxane, toluene, THF and ethyl acetate) as reaction media, strong oxidants, 'pure' oxygen environment, prolonged heating condition, green LED as irradiation source etc. are yet to Scheme 6.…”
Section: Visible Light Induced Photocatalytic Synthesis Of 2-quinazolinesmentioning
confidence: 99%
“…reported an example of a highly dispersed nickel NPs supported on N,P‐codoped porous carbon (Ni 2 P@NPC‐800) catalysed synthesis of N‐heterocycles under atmospheric air and mild reaction conditions (Scheme 21). [36] The as‐prepared catalyst has demonstrated outstanding catalytic activities to afford quinazolines, quinazolinones, and imidazoles via oxidative cross‐dehydrogenative coupling of alcohols and diamines or 2‐aminobenzamides under milder reaction conditions. In addition, high catalytic activity, good functional group tolerance, broad substrate scopes, strong stability, operationally and easy handling was achieved for the synthesis of pharmaceutically important N‐heterocycles.…”
Section: Direct Functionalization Of C−h Bondmentioning
confidence: 99%
“…With the great advance, considerable recent progress has been achieved in the development of support materials for supported NPs based heterogeneous catalysts. The majority of the support materials are silica [15–21] metal‐oxides [22–30] carbon‐based materials [31–36] and metal‐organic frameworks (MOFs) [37–40] . It has been reported that the catalytic activities of supported metal NPs catalysts can be tuned using a variety of metal‐support interaction types [10,41] .…”
Section: Introductionmentioning
confidence: 99%
“…The Ni 2 P NP-supported biomass-derived N,P co-doped porous carbon (Ni 2 P@NPC-800)-catalyzed cross-dehydrogenative coupling of alcohols (254) with diamines (33a or 6h) or oamino benzamides (133e) was reported for the synthesis of benzimidazoles (84d), quinazolines (32b) and quinazolinones (134c), respectively (Scheme 138). 264 The catalyst was prepared via the hydrothermal and pyrolysis treatment of the biochar of bamboo shoots with Ni(OAc) 2 and phytic acid as Ni and P sources, respectively. The control experiments gave insight into the reaction mechanism, in which the catalyst assists in the oxidation of alcohol to aldehydes and aromatization to the nal compounds.…”
Section: Ninp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%